Domain‐general and domain‐specific functional networks of Broca's area underlying language processing - Talat Bulut (Brain and Behavior, 2023)
Abstract Introduction Despite abundant research on the role of Broca's area in language processing, there is still no consensus on language specificity of this region and its connectivity network. Methods The present study employed the meta‐analytic connectivity modeling procedure to identify and compare domain‐specific (language‐specific) and domain‐general (shared between language and other domains) functional connectivity patterns of three subdivisions within the broadly defined Broca's area: pars opercularis (IFGop), pars triangularis (IFGtri), and pars orbitalis (IFGorb) of the left inferior frontal gyrus. Results The findings revealed a left‐lateralized frontotemporal network for all regions of interest underlying domain‐specific linguistic functions. The domain‐general network, however, spanned frontoparietal regions that overlap with the multiple‐demand network and subcortical regions spanning the thalamus and the basal ganglia. Conclusions The findings suggest that language specificity of Broca's area emerges within a left‐lateralized frontotemporal network, and that domain‐general resources are garnered from frontoparietal and subcortical networks when required by task demands.